Surface Engineering of Escherichia coli–Derived OMVs as Promising Nano-Carriers to Target EGFR-Overexpressing Breast Cancer Cells - Sepahdar, Zahra; Miroliaei, Mehran; Bouzari, Saeid; Khalaj, Vahid; Salimi, Mona (Frontiers in Pharmacology, 2021)
Bacterial outer membrane vesicles (OMVs) have recently drawn a great deal of attention due to their therapeutic efficiency and ability to target specific cells. In the present study, we sought to probe engineered OMVs as novel and promising carriers to target breast cancer cells. Following the fusion of the affiEGFR-GALA structure to the C- terminal of ClyA as an anchor protein, the ClyA-affiEGFR-GALA construct was successfully expressed on the surface of ∆msbB/∆pagP E. coli W3110-derived OMVs. Morphological features of the engineered and wild-type OMVs were identical. The engineered OMVs induced no endotoxicity, cytotoxicity or immunogenicity, indicating the safety of their application. These OMVs could specifically bind to EGF receptors of MDA-MB-468 cells expressing high levels of EGFR, and not to those with low levels of EGFR (HEK293T cells). Interestingly, despite a lower binding affinity of the engineered OMVs relative to the positive control Cetuximab, it was strong enough to identify these cells. Moreover, confocal microscopy revealed a significant uptake of the modified OMVs by the EGFR-overexpressing cells in the absence and presence of EGFR competitors. These results suggest that OMVs might internalize into the cells with EGF receptors, as no OMVs entered the cells with any EGFR expression, or those pretreated with EGF or Cetuximab. Regarding the EGFR-binding affinity of the engineered OMVs and their cellular uptake, they are presented here as a potential carrier for cell-specific drug-delivery to treat a wide variety of cancer cells. Interestingly, the engineered OMVs are capable of reaching the cytoplasm while escaping the endosome due to the incorporation of a fusogenic GALA peptide in the construct.